FEATURES AND ROLE OF MARKETING OF AGRICULTURAL ENTERPRISES IN THE CONTEXT OF THEIR COMPETITIVE DEVELOPMENT - SERHIIENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The conducted research determines the important aspects of the role of marketing in the activities of agricultural enterprises in the conditions of growing competition. Agricultural marketing is considered as a system of managing the activities of agricultural companies, which ensures the regulation of market processes and the study of the agricultural market, creates conditions for determining the needs of consumers and the possibilities of their satisfaction in the conditions of modern challenges. The stages of the development of agricultural marketing, starting from the processes of agro-industrialization, are defined. It has been studied that in the process of evolution, the understanding of agricultural marketing changes, in connection with certain institutional and technical limitations of the agrarian sphere, its limited opportunities for managing the marketing complex. In modern conditions, marketing is a leading concept in the formation of relationships between producers and consumers of agricultural products. It was determined that in the scientific literature there are various interpretations of marketing in the agricultural sphere, such as "marketing in agriculture", "agricultural marketing", "marketing in the agro-industrial sphere". The scientific approaches to understanding the definition of "agrarian marketing" are summarized and the following are distinguished: production, functional, system, and effective approaches, with researchers specifying each approach. It is substantiated that agrarian marketing due to the specificity of the agricultural industry is more complicated in comparison with other types of marketing, and the personalities and key challenges for the agrarian sphere, which affect the practical implementation of agrarian marketing, are singled out. The existing scientific approaches to the classification of agricultural marketing functions were summarized and supplemented with new agricultural marketing functions that were updated during the war: communication, adaptive, social. The main purpose of agricultural marketing in today’s conditions is substantiated, which consists in building an optimal system of goods movement and positioning of manufactured products both on domestic and international markets.